Kebijakan Kebijakan Implementasi Merdeka Belajar pada Mata Pelajaran ISMUBA di Era Disrupsi Sosial dan Revalusi Industri 5.0: - - Rahmad Salahuddin Tri Putra; Sri Utami; Abdul Haris (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
The policy of independent learning as a basis for education and teaching in ISMUBA subjects is very important, considering that the assessment of education in terms of minimum abilities, including literacy, numeracy and character surveys, is carried out not only as a test but also as a search for the extent to which the values of character, religion and Pancasila are implemented. has been practiced by students in everyday life. Therefore, the aim of this research is: to describe the implementation of freedom of learning in the development of the ISMUBA education curriculum, as well as to describe the policy for implementing the ISMUBA education curriculum into learning activities that reflect freedom of learning. Data collection methods used in this exploratory-qualitative research include in-depth interviews and document studies for further analysis using the Miles and Huberman model of triangulation approach. The results of this research illustrate that; First, Merdeka learning is applied in curriculum development through the process of aligning the ISMUBA education curriculum between the 2017 National Curriculum, the PP Muhammadiyah curriculum in 2017 and the East Java PWM curriculum as a result of the conversion in 2014 to give birth to the 2017 East Java ISMUBA PWM Education curriculum which will be refined in 2022; Second, Merdeka learning is also applied in the learning implementation and assessment system which focuses on independent learning. Where the learning system uses a scientific approach and assessment using authentic assessment and diagnostic tests based on literacy and numeracy